Fabrication and characterization of Cu-Sn-Ni-Cu interconnection microstructure for electromigration studies in 3D integration. Issue 2 (4th April 2016) - Xiao, Ming; Munief, Walid Madhat; Wu, Fengshun; Lilischkis, Rainer; Oberbillig, Tobias; Saumer, Monika; Xia, Weisheng
Abstract : Purpose: The purpose of this paper is to fabricate a new Cu-Sn-Ni-Cu interconnection microstructure for electromigration studies in 3D integration. Design/methodology/approach: The Cu-Sn-Ni-Cu interconnection microstructure is fabricated by a three-mask photolithography process with different electroplating processes. This microstructure consists of pads and conductive lines as the bottom layer, Cu-Sn-Ni-Cu pillars with the diameter of 10-40 μm as the middle layer and Cu conductive lines as the top layer. A lift-off process is adopted for the bottom layer. The Cu-Sn-Ni-Cu pillars are fabricated by photolithography with sequential electroplating processes. To fabricate the top layer, a sputtered Cu layer is introduced to prevent the middle-layer photoresist from being developed. With the final Cu electroplating processes, the Cu-Sn-Ni-Cu interconnection microstructure is successfully achieved. Findings: The surface morphology of Cu-Sn pillars consists of densely packed clusters which are formed by an ordered arrangement of tetragonal Sn grains. The diffusion of Cu atoms into the Sn phases is observed at the Cu/Sn interface. Furthermore, the obtained Cu-Sn-Ni-Cu pillars have a flat surface with an average roughness of 13.9 nm. In addition, the introduction of Ni layer between the Sn and the top Cu layers in the Cu-Sn-Ni-Cu pillars can mitigate the diffusion of Cu atoms into Sn phases. The process is verified by checking the electrical performance using four-point probe measurements. Originality/value: The method described in this paper which combined a three-mask photolithography process with sequential Cu, Sn, Ni and Cu electroplating processes provides a new way to fabricate the interconnection microstructure for future electromigration studies.